Does nature-based solution sustain grassland quality? Evidence from rotational grazing practice in China - Dong-qing LI; Ming-xue ZHANG; Xin-xin LÜ; Ling-ling HOU (Journal of Integrative Agriculture)
Rotational grazing is considered as one of the nature-based solutions (NbS) to grassland protection by natural scientists. However, its effects on improving grassland quality are still unclear when it is adopted by herders. Using a household-level panel data from field survey in two main pastoral provinces of China, empirical results from fixed-effect model and instrumental approach show that rotational grazing practices have insignificant short-term effects on grassland quality, but have positive long-term effects. In addition, rotational grazing practices can improve grassland quality when villages invest public infrastructure or herders have private supporting measures for more efficiency livestock production. Further analysis shows that herders adopting rotational grazing have higher grazing intensity, higher supplementary intensity and more livestock-house-feeding days, which indicate herders can utilize more efficient livestock management without increasing pressure on natural grassland. We also find that herders with pastoral income are more likely to adopt rotational grazing practice. These insightful findings offer policy implications on promoting grassroot NbS for ecosystem protection and resource utilization in developing pastoral countries.